2015
DOI: 10.1186/s41043-015-0023-z
|View full text |Cite
|
Sign up to set email alerts
|

From home deliveries to health care facilities: establishing a traditional birth attendant referral program in Kenya

Abstract: ObjectiveTo assess the effectiveness of a traditional birth attendant (TBA) referral program on increasing the number of deliveries overseen by skilled birth attendants (SBA) in rural Kenyan health facilities before and after the implementation of a free maternity care policy.MethodsIn a rural region of Kenya, TBAs were recruited to educate pregnant women about the importance of delivering in healthcare facilities and were offered a stipend for every pregnant woman whom they brought to the healthcare facility.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 8 publications
0
24
0
1
Order By: Relevance
“…A paper by Maina and Kirigia ( 2015 ) shows increases in public sector deliveries post-policy, yet this finding is based on facility surveys from a subset of counties. Conversely, Tomedi et al ( 2015 ) collected data from 29 rural primary-level health facilities in Machakos County and did not show a significant increase in skilled birth attendant deliveries in a 7 month period after introduction of the policy. These two studies had a limited geographic range and highlight the need for population-based evidence.…”
Section: Discussionmentioning
confidence: 94%
“…A paper by Maina and Kirigia ( 2015 ) shows increases in public sector deliveries post-policy, yet this finding is based on facility surveys from a subset of counties. Conversely, Tomedi et al ( 2015 ) collected data from 29 rural primary-level health facilities in Machakos County and did not show a significant increase in skilled birth attendant deliveries in a 7 month period after introduction of the policy. These two studies had a limited geographic range and highlight the need for population-based evidence.…”
Section: Discussionmentioning
confidence: 94%
“…The 17 studies were conducted in 12 countries in Africa, these being grouped as following: one conducted in three countries (Ethiopia, Ghana and Nigeria)(Wells et al, 2016 ), two in Ethiopia (Molla et al, 2015 ; Tesfahun et al, 2014 ), two in Ghana (Hill et al, 2015 ; Oduro‐Mensah et al, 2013 ) and one in Nigeria (Agho et al, 2016 ). Two were conducted in Kenya (Byrne et al, 2016 ; Tomedi et al, 2015 ), two in Tanzania (Kanté et al, 2015 ; Pfeiffer & Mwaipopo, 2013 ) and one each in Burkina‐Faso (De Allegri et al, 2015 ), DRC/Congo (Ntambue et al, 2016 ), Niger (Bensaïd et al, 2016 ), Rwanda (Hagey et al, 2014 ), South Africa (Haddad et al, 2016 ), Uganda (Ahumuza et al, 2016 ) and Zambia (Kyei et al, 2012 ) (Table 1 ). As indicated in Table S3 , the appraisal of the 17 studies confirmed that they could all be used in the review, as the methods sections provided sufficient detail to extract the type of information required to effectively use the MMAT tool.…”
Section: Resultsmentioning
confidence: 99%
“…Mothers’ use of TBAs remains higher than SBAs in remote areas that have few health facilities and where mobile populations have limited access to static health services (Byrne et al, 2016 ). TBAs were too far away from health centres to improve the transfer of mother to the SBAs in rural Kenyan health facilities both before and after the implementation of a free maternity care policy in 2013 (Tomedi et al, 2015 ). The finding showed that at Phomolong clinic near Kalafong Hospital in peri‐urban Pretoria (South Africa), pregnant women delayed their attendance of ANC visits until late in their pregnancy, making intervention planning difficult (Haddad et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…TRADITIONAL birth attendants (TBAs) have long been used by women in East Africa to aid in childbirth (1)(2)(3)(4)(5). TBAs typically have no formal education and often engage in unregulated use of medicinal plants as well as other ritualistic but culturally acceptable practices.…”
Section: Introductionmentioning
confidence: 99%